Rescue and Optimization of Underperforming Clinical Trial Sites in High-Stakes Oncology Studies - Chisom Ezeanochie; Opeoluwa Oluwanifemi Akomolafe; Christiana Adeyemi (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Oncology clinical trials are central to advancing cancer treatment, yet many face delays and risks of failure due to underperforming trial sites. Rescue and optimization strategies for these sites are essential to preserving study integrity, safeguarding patient outcomes, and accelerating therapeutic innovation. This paper examines approaches to revitalizing underperforming clinical trial sites in high-stakes oncology studies, where timeliness and data quality are critical. Common challenges at such sites include inadequate patient recruitment, protocol deviations, high data query rates, and insufficient adherence to Good Clinical Practice (GCP) standards. These issues not only compromise study timelines but also threaten the validity of trial outcomes. Effective rescue interventions require a multidimensional framework that combines site performance assessment, rapid root cause analysis, and tailored remediation plans. Key strategies include deploying specialized rescue teams, enhancing site staff training, leveraging centralized monitoring tools, and improving communication pathways between sponsors, contract research organizations (CROs), and investigators. The integration of digital technologies, such as real-time data analytics, risk-based monitoring, and artificial intelligence, further supports the identification of performance gaps and predictive modeling of potential risks. Additionally, fostering a culture of accountability and collaboration ensures that corrective measures are sustainable and aligned with regulatory requirements. Case insights demonstrate that proactive optimization not only restores site performance but also strengthens patient recruitment, enhances data integrity, and improves trial efficiency. Importantly, these strategies reduce costs associated with trial delays, mitigate regulatory risks, and ultimately accelerate the delivery of life-saving oncology therapies to patients. This research underscores the critical role of site rescue and optimization in ensuring that high-stakes oncology studies achieve their scientific and clinical goals, while highlighting the need for continuous innovation, adaptive trial management, and strong stakeholder engagement.